Ibu Kota Negara (IKN) dan Mitigasi Ancaman Terorisme: Pendekatan Kesejahteraan untuk Pencegahan Aksi Kejahatan di Indonesia - Annisa Yudha Apriliasari; Sapto Priyanto (UNES Law Review, 2024)
The relocation of the National Capital (Ibu Kota Negara/IKN) to East Kalimantan Province has sparked pros and cons regarding potential threats and ways of countering terrorism in the new capital city, called Nusantara. This paper aims to provide a design and framework for mitigating the threat of terrorism in the nation's capital city by using a welfare criminology approach. This paper uses a qualitative approach regarding secondary data sourced from statistical data publications, online media news, journal articles, and previous similar research/studies. The new IKN with the name Nusantara which carries the concept of a "smart city" based on cyber technology, faces the challenge of the threat of terror acts in a hybrid manner. The government needs to design an integrated prevention and counterterrorism strategy in IKN Nusantara and its surrounding areas that is not only cyber-based, but also relies on natural surveillance from the surrounding communities, and in the policy-making process needs to consider the situation of the community and existing local wisdom. The welfare approach can also be in line with the aim of addressing the root causes of radicalization and conflict, such as economic marginalization, social and cultural issues.